Hubungan dukungan keluarga terhadap keberhasilan teknik menyusui di Ruang Ranap Ibu RSIA Muslimat Jombang - Suparni, Ita; Rahma Syafarina, Angelia (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2025)
Breastfeeding is one of the best investments for survival and improving health, social and economic development of individuals and the nation. Successful breastfeeding is a joint effort that requires correct information and strong support to create an environment that allows mothers to breastfeed optimally. One of the factors for successful breastfeeding is family support. This study aims to determine the relationship between family support and the success of breastfeeding techniques in the Mother's Residential Room of RSIA Muslimat Jombang. This study uses an analytical survey method with a cross-sectional approach. The population in this study were 155 postpartum mothers in January-February 2024. The research sample was postpartum mothers in the Nursing Home Room of RSIA Muslimat Jombang in May-June 2024 totaling 61 respondents with a simple random sampling technique. The independent variable is family support and the dependent variable is the success of breastfeeding techniques. The research instrument used a questionnaire. Data analysis used Chi Square with SPSS. The results of the study showed that most mothers with high family support were 40 people (49.2%), and most mothers were successful in carrying out breastfeeding techniques, namely 34 people (55.7%). It was significant with a value of p = 0.001 or p <0.05, OR = 7.250, CI 95% (2.15 to 24.44). Where mothers with high family support experienced success in breastfeeding 7,250 times compared to mothers with low family support. Family support affects the success of breastfeeding techniques. Breastfeeding mothers who get family support feel more comfortable and safe which can affect the mother's hormonal system. The mother's emotions and psychological state greatly affect the milk flow reflex. Thus increasing success in breastfeeding Keywords: Family Support, Successful Breastfeeding Techniques, Postpartum Mothers